2017
DOI: 10.1016/j.psychres.2017.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-related distress and its associated factors among patients with type 2 diabetes mellitus in China

Abstract: Diabetes-related distress is one of the psychological disorders affecting patients with diabetes, yet there are few studies about diabetes-related distress in Chinese patients. To assess the level of psychological distress and examine its associated factors, we conducted a cross-sectional analysis of patients with type 2 diabetes mellitus from a Chinese tertiary hospital. The Diabetes Distress Scale (DDS) and the General Self-Efficacy Scale (GSES) were administered. There were 210 (57.85%) patients with little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
57
9
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 32 publications
16
57
9
2
Order By: Relevance
“…Prevalence of distress in other Asian countries was reported to be higher, ranging from 19-23%. 6,7 A study conducted in South Africa revealed that 44% of subjects suffered from moderate to high level of distress and also higher scores of emotional burden dimension and regimen distress, in congruence with the study results. 10 In a North Indian study by Gahlan, et al the prevalence was 18% with the highest subscale being emotional burden dimension.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Prevalence of distress in other Asian countries was reported to be higher, ranging from 19-23%. 6,7 A study conducted in South Africa revealed that 44% of subjects suffered from moderate to high level of distress and also higher scores of emotional burden dimension and regimen distress, in congruence with the study results. 10 In a North Indian study by Gahlan, et al the prevalence was 18% with the highest subscale being emotional burden dimension.…”
Section: Discussionsupporting
confidence: 82%
“…Here the distress has more prevalence than depression in a diabetes individual, and other than HbA1c, factors like age, gender treatment adherence and social support also has an influence on the distress. 6 Advanced age, being unmarried, having more complications and co morbidities, having less family support, and being depressed are associated with higher levels of distress. 7 In order to maintain better glycaemic control, good diabetes self-care behaviours like patient's knowledge and physical skills, and social and emotional factors should be favourable.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study conducted in USA (Fisher et al, 2012) using the DDS-17 scale showed that 51.3% of the screened participants have moderate to high DRD. Similar distress proportions were shown from the studies conducted in Bangladesh (48.5%), China (43%) and Canada (39%) using DDS-17 (Islam et al, 2013;Wong et al, 2017;Zhou et al, 2017). Emotional burden was considered as the most important domain in measuring diabetes distress especially among women.…”
Section: Discussionsupporting
confidence: 76%
“…Karakteristik sosio-demografi responden secara detail, disampaikan pada tabel 1. Lloyd, Smith, & Weinger, 2005;Zhou et al, 2017). Fenomena tentang stres pada penyandang DM cenderung diidentifikasi sebagai hal yang baru dibandingkan dengan gangguan psikologis lain yang pernah ditemukan (Rariden, 2019).…”
Section: Hasilunclassified